Gender Sensitization in Panipat City - Geeta (Innovative Research Thoughts, 2018)
Gender sensitization is an important condition for the standard development of a human. The need for sensitivity has been felt and realized since times immemorial, in almost all kinds of human existence all over the world. Being essential from the point of sustainable development, this topic has represent a lot of attention of early. There is an effort to look into the concept of gender sensitization. Looking at the historical background, it is clear that in early times Indian society was sensitized and women had equality .They were learned women as Sita, Gargi, Maitreyi and Aruni. In medieval times the place of women in society has started decaying with some rigid customs were followed as sati pratha, child marriage .After independence in India both men and women have been given equal rights under the Indian Constitution. However, despite making progress and occupying some vital positions, Indian women are still a censored with the problem being more acute in the rural areas. This retain the gender sensitization process in India.